Pengembangan Bahan Ajar BIPA pada Keterampilan Menulis Cerpen Tingkat Dasar Bermuatan Budaya Indonesia dengan Media Audiovisual - Sintia, Haqsir Venny; Muliastuti, Liliana; Eriyani, Reni Nur (Kajian Bahasa dan Sastra (KABASTRA), 2023)
This article discusses the application of teaching materials to a BIPA (Indonesian Language for Foreign Speakers) teaching, especially in reading skills through a culturally charged audiovisual learning medium. The purpose of this study was to explain teaching materials delivered in culturally charged audiovisual media at the basic level of BIPA teaching with short story writing skills. Audiovisual media pages also accommodate the needs of online BIPA learning. This audiovisual media can be in the form of dialogue videos and explanation videos, as well as supporting media in the form of materials or handbooks. The research method used is descriptive qualitative. The reference source used here is in the form of the BIPA AI guidebook "Sahabatku Indonesia" published by the Language Agency of the Ministry of Education and Culture. The technique for checking the validity of the data in this study used a method triangulation technique by checking the understanding of lecturers and students on the use of audiovisual media containing Indonesian culture in short story writing skills. The conclusion of this study is that BIPA teaching materials, especially writing skills, use audiovisual media with Indonesian culture in short story writing skills at the basic level. This teaching material is quite helpful in providing a breakthrough and can make it easier for BIPA students to understand the material presented as well as being able to introduce cultures in Indonesia. Thus, it is hoped that with this media it can be used as a source of inspiration in further, more complete research. and innovative.